Well‐being in the Welfare State: the redistributive capacity of education. (December 2016) - Jongbloed, Janine; Pullman, Ashley
Abstract: Focusing on the macro‐micro interaction between institutional arrangements and individual life outcomes, this article investigates how welfare régime types impact the association between education and well‐being, as measured by satisfaction with life. Theorising with Esping‐Andersen's ideal‐typical welfare régime typology, we hypothesise that decommodified institutional arrangements reduce the association between education and well‐being through compensatory social protections for at‐risk individuals, while stratifying forces strengthen this association. These results are only partly supported; we find that Conservative Welfare States show the most robust association, whilst Liberal and Social‐Democratic Welfare States display weaker relationships. Thus, stratification appears to play a more important role than decommodification in moderating this association. We also examine potential mediating factors and how they differ between welfare régime types, finding that health and income mediate the effects of education on well‐being to varying degrees.